2017
DOI: 10.1016/j.actatropica.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the spermathecae of twelve species of Triatominae (Hemiptera, Reduviidae) vectors of Chagas disease

Abstract: Trypanosoma cruzi, the etiological agent of Chagas disease, is transmitted by triatomines that have been described in a large number of studies. Most of those studies are related to external morphology and taxonomy, but some biochemical, genetic and physiological studies have also been published. There are a few publications in the literature about the internal organs of Triatominae, for instance the spermathecae, which are responsible for storing and maintaining the viability of the spermatozoids until the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…nov. (more specifically in the structures of the eighth ventral segment as well as between setae) were observed [ 54 ]. Furthermore, Nascimento et al [ 55 ] also observed similarities between spermathecae morphology from P. lignarius, P. megistus and P. tibiamaculatus comb. nov., and Mello et al [ 56 ] recorded a relationship between exocorial cells in eggs of P. tibiamaculatus comb.…”
Section: Discussionmentioning
confidence: 95%
“…nov. (more specifically in the structures of the eighth ventral segment as well as between setae) were observed [ 54 ]. Furthermore, Nascimento et al [ 55 ] also observed similarities between spermathecae morphology from P. lignarius, P. megistus and P. tibiamaculatus comb. nov., and Mello et al [ 56 ] recorded a relationship between exocorial cells in eggs of P. tibiamaculatus comb.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that female triatomines can store sperm for months or years, however, studies of this are scarce (Vöcking et al 2013, Nascimento et al 2017). We observed a female T. pallidipennis since her capture, and the number of fertile laid eggs showed that it had previously copulated before being captured.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important confirmation considering that sensitivity to contaminants and histopathological changes induced by contamination can vary within a wide range, depending on the species (Bernet, Schmidt, Meier, Burkhardt‐Holm, & Wahli, ; Glover et al, ). Taxonomically, several studies have shown that the study and analysis of the internal morphology of insects is a useful tool for this group's systematics (Deans, Mikó, Wipfler, & Friedrich, ; Nascimento et al, ), including Diptera (King, ; King, ; Kotrba, ; Mazurkiewicz & Kubrakiewicz, ). The taxonomic identification of species of the genus Chironomus has been a challenge for experts of this group, due to the external morphological similarity among species (Lindeberg & Wiederholm, ).…”
Section: Discussionmentioning
confidence: 99%